An innovative gene expression modulating strategy by converting nucleic acids into HNC therapeutics using carrier-free nanoparticles - Liu, Heyuan; Huang, Yinong; Li, Zongfang; Han, Suxia; Liu, Tianya; Zhao, Qian (Frontiers in Immunology, 2024)
Background: Cell fate and microenvironmental changes resulting from aberrant expression of specific proteins in tumors are one of the major causes of inadequate anti-tumor immune response and poor prognosis in head and neck cancer (HNC). Eukaryotic initiation factor 3C (eIF3c) has emerged as a promising therapeutic target for HNC due to its ability to regulate protein expression levels in tumor cells, but its drug development is difficult to achieve by targeting traditional protein-protein interactions. siRNA has emerged as a highly promising modality for drug development targeting eIF3c, while its application is hindered by challenges pertaining to inadequate stability and insufficient concentration specifically within tumor sites.We employed a method to convert flexible siRNAs into stable and biologically active infinite Auric-sulfhydryl coordination supramolecular siRNAs (IacsRNAs). Through coordinated self-assembly, we successfully transformed eIF3C siRNAs into the carrier-free HNC nanotherapeutic agent Iacs-eif3c-RNA. The efficacy of this agent was evaluated in vivo using HNC xenograft models, demonstrating promising antitumor effects.Results: Iacs-eif3c-RNA demonstrated the ability to overcome the pharmacological obstacle associated with targeting eIF3C, resulting in a significant reduction in eIF3C expression within tumor tissues, as well as effective tumor cell proliferating suppression and apoptosis promotion. In comparison to monotherapy utilizing the chemotherapeutic agent cisplatin, Iacs-eif3c-RNA exhibited superior anti-tumor efficacy and favorable biosafety.The utilization of Iacs-eif3c-RNA as a carrier-free nanotherapeutic agent presents a promising and innovative approach for addressing HNC treating challenges. Moreover, this strategy demonstrates potential for the translation of therapeutic siRNAs into clinical drugs, extending its applicability to the treatment of other cancers and various diseases.